2011
DOI: 10.1155/2011/204639
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Application of New Ruthenium Complexes Containingβ-Diketonato Ligands as Sensitizers for Nanocrystalline TiO2Solar Cells

Abstract: Five heteroleptic ruthenium complexes having differentβ-diketonato ligands, [Ru(tctpy)(dppd)(NCS)] (1), [Ru(tctpy)(pd)(NCS)] (2), [Ru(tctpy)(tdd)(NCS)] (3), [Ru(tctpy)(mepd)(NCS)] (4), and [Ru(tctpy)(tmhd)(NCS)] (5), where tctpy = 4,4′,4′′-tricarboxy-2,2′:6′,2′′-terpyridine, pd = pentane-2,4-dione, mepd = 3-methylpentane-2,4-dione, tmhd = 2,2,6,6-tetramethylheptane-3,5-dione, tdd = tridecane-6,8-dione, and dppd = 1,3-diphenylpropane-1,3-dione, were synthesized and characterized. These heteroleptic complexes ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…A series of β-diketonate ligands ( 31 in Figure 25 ) was investigated by Islam et al [ 119 , 120 , 121 , 122 , 123 , 124 , 125 ] as ancillary ligands alternative to thiocyanates in the BD structure. The strong σ-donating nature of the negatively-charged oxygen donor atom destabilizes the ground-state energy level of the dye compared to BD, leading to a shift of the MLCT transitions to lower energies.…”
Section: Modifications Of Black Dye and Structure-properties Relatmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of β-diketonate ligands ( 31 in Figure 25 ) was investigated by Islam et al [ 119 , 120 , 121 , 122 , 123 , 124 , 125 ] as ancillary ligands alternative to thiocyanates in the BD structure. The strong σ-donating nature of the negatively-charged oxygen donor atom destabilizes the ground-state energy level of the dye compared to BD, leading to a shift of the MLCT transitions to lower energies.…”
Section: Modifications Of Black Dye and Structure-properties Relatmentioning
confidence: 99%
“…A very efficient sensitization ( η = 9.1%; TiO 2 : 20 μm, dye: 0.2 mM CH 3 CN / t -butanol 1:1 with 20 mM DCA, electrolyte: 0.6 M DMPII, 0.05 M I 2 , 0.1 M LiI, 0.07 M t-bupy in CH 3 CN), with an IPCE greater than 80% in the whole visible range extending up to 950 nm was obtained. Further substituted β-diketonate ligands were tested in 2011 [ 119 ] showing a great potential to tune the photochemical properties.…”
Section: Modifications Of Black Dye and Structure-properties Relatmentioning
confidence: 99%
“…Moreover, whether iodine regenerates the dye practically at 100% yield is another challenge [48]. The synthesis of a series of ruthenium polypyridyl complexes allowing the systematic tuning of the LUMO sensitizer for easy injection of the excited electrons to the semiconductor oxide and HOMO energy level of the sensitizer for efficient dye regeneration has been reported in the literature [49]. The possibility of tuning the MLCT energy has led to the preparation of many different organocompounds that have been investigated for semiconductor sensitization.…”
Section: Research Development On Metal Complexes For Dye-sensitized Smentioning
confidence: 99%
“…(1) and reported that these solar cells have an enhanced red response in the near-IR region, but the solar cell performance was decreased due to the poor electron injection efficiency on to TiO 2 [8]. As a part of our research program in the development of new photosensitizers [9][10][11][12][13][14], we have strategically designed a heteroleptic dye SPS-02 ( Figure 1) having both 4,4 ′ -di-tert-butyl-2-2 ′ -dipyridyl and 4,4 ′ -dicarboxy-2,2 ′ -biquinoline in the same molecule, which exhibits better performance in the IR region.…”
Section: Introductionmentioning
confidence: 99%